THE LEGAL STATUS AND LEGAL PROTECTION TOWARDS CLIMATE REFUGEES UNDER INTERNATIONAL LAW: A STUDY OF IOANE TEITIOTA CASE - Najla Nur Fauziyah (BELLI AC PACIS (Jurnal Hukum Internasional), 2023)
This study aims to examine the legal status of climate refugees in international law according to the Ioane Teitiota case and how international law in general protects climate refugees. This study is a normative legal research. The types of approach used are statute, case, and conceptual approaches. The legal materials of this study comprise of primary, secondary, and tertiery legal materials. In collecting data this study used the library research data collection technique. The analysis technique used is the inductive reasoning method. The results of this study reveal that the 1951 Refugee Convention is unable to accommodate climate refugees. However, UN Human Rights Committee in its reccomendation acknowledges the effects of climate change as one of the determining factor for the affected persons to seek asylum in other countries which triggers the enforcement of non-refoulement principle. The protection under international law towards climate refugees derive from state obligation to comply with the non-refoulement principle, ad hoc aids from other states influenced by Nansen Initiative’s Protection Agenda, and the tangible protections provided by UNHCR and its cooperation with local authorities.